Animal-Human Relationships in Medieval Iceland : From Farm-Settlement to Sagas - Evans Tang, Harriet J. (D.S. Brewer, 2022)
A multi-disciplinary investigation of the links between people and animals, in reality and representation.
Keywords: Icelandic literature -- History and criticism.; Human-animal relationships in literature.; Human-animal relationships -- Iceland -- History -- To 1500.; Agriculture -- Iceland -- History -- To 1500.; Littérature islandaise -- Histoire et critique.; Relations humain-animal dans la littérature.; Agriculture -- Islande -- Histoire -- Jusqu'à 1500.; Icelandic literature; Human-animal relationships in literature; Agriculture; Human-animal relationships; Iceland; To 1500; Criticism, interpretation, etc.; History